The importance of plant diversity in maintaining the pollinator bee, Eulaema nigrita (Hymenoptera: Apidae) in sweet passion fruit fields - da Silva, Cláudia Inês; Gomes Bordon, Natali; da Rocha Filho, Léo Correia; Garófalo, Carlos Alberto (Revista de Biología Tropical, 2012)
The euglossine bee Eulaema nigrita plays an important role for the pollination of native and economically important plants, such as the sweet passion-fruit Passiflora alata. E. nigrita uniquely collects the nectar from the flowers of P. alata, nevertheless, it needs to visit other plants to collect pollen, nectar and other resources for its survival. There are two methods to identify the species of plants used by bees in their diet: by direct observation of the bees in the flowers, and through identification of pollen grains present in brood cells, feces, or in the bees’ body. In order to identify the other plants that E. nigrita visits, we analyzed samples of pollen grains removed from the bee’s body in the course of the flowering period of P. alata. Among our results, the flora visited by E. nigrita comprised 40 species from 32 genera and 19 families, some of them used as a pollen source or just nectar. In spite of being a polyletic species, E. nigrita exhibited preference for some plant species with poricidal anthers. P. alata which has high sugar concentration nectar was the main source of nectar for this bee in the studied area. Nonetheless, the pollinic analysis indicated that others nectariferous plant species are necessary to keep the populations of E. nigrita. Studies such as this one are important since they indicate supplementary pollen-nectar sources which must be used for the conservation of the populations of E. nigrita in crops neighbouring areas. In the absence of pollinators, growers are forced to pay for hand pollination, which increases production costs; keeping pollinators in cultivated areas is still more feasible to ensure sweet passion fruit production.